Dispatcher-Assisted Cardiopulmonary Resuscitation: Disparity between Urban and Rural Areas. (1st June 2020) - Chen, Yen-Chin; Yu, Shao-Hua; Chen, Wei-Jen; Huang, Li-Chi; Chen, Chih-Yu; Shih, Hong-Mo
Abstract : Object . To compare the provision and effectiveness of dispatcher-assisted cardiopulmonary resuscitation (DACPR) in rural and urban areas. Methods . Patients with out-of-hospital cardiac arrest (OHCA) were prospectively registered in Taichung. The 29 districts of Taichung city were divided into urban and rural areas based on whether the population density is more than 1, 000 people per square kilometer. Prehospital data were collected according to the Utstein-style template, and telephone auditory records were collected by a dispatch center. Results . 2, 716 patients were enrolled during the study period. 88.4% OHCA occurred in urban areas and 11.6% in rural areas. 74.9% after dispatcher assistance, laypersons performed CPR in urban areas and 67.7% in rural areas (p = 0.023 ). The proportion of laypersons continued CPR until an emergency medical technician's (EMT) arrival was higher in the urban areas (59.57% vs 52.27%, p = 0.039 ). Laypersons continued CPR until an EMT' arrival would increase the chance of return of spontaneous circulation in urban and rural areas, with adjusted odds ratio (aOR) of 1.02, 95% confidence interval (CI) of 0.82–1.27, and aOR of 1.49, 95% CI of 0.80–2.80, respectively. Continued laypersons CPR until the EMT' arrival also improved survival with favorable neurological function, with aOR of 1.16, 95% CI of 0.61–2.20 in urban areas and aOR of 2.90 95% CI of 0.18–46.81 in rural areas. Conclusion . Bystanders in urban areas exhibited higher ratio of acceptance of DACPR. However, after DACPR intervention, prognosis improvement was considerably higher in rural areas than in urban areas.